Effects of Development Interventions on the Productivity and Profitability of Women Shea Butter Processors in the West Gonja District of Northern Ghana - Abujaja , Afishata Mohammed; Adam , Hamza; Zakaria , Hudu (Asian Journal of Agriculture and Rural Development, 2013)
This paper examines the effects of development agencies’ interventions on productivity and profitability of women shea butter processors in contributing to the development of the shea nut industry in Northern Ghana. A survey of 114 women shea butter processors, comprising of 57 each of both beneficiaries and non-beneficiaries of development interventions in the West Gonja District were sampled and interviewed with a semi structured questionnaire. Focus group discussions were also held to obtain qualitative data. Results of Analysis of Variance (ANOVA) conducted at 5% level of significance found that labour productivity of beneficiaries of development interventions by way of training, equipment and machinery provisions do not differ significantly from that of respondents who had never benefited from such interventions. Similar results were found with regard to average monthly profit made by beneficiaries and non-beneficiaries. Market sourcing was identified as a major problem affecting women shea butter processors in the district. The study therefore recommends that development agencies programs should highlight follow-up trainings, monitoring and supervisions to ensure the sustainability of projects so that they can continue to yield expected impacts. Also, development agents should include market sourcing opportunities in rural enterprise improvement interventions since that remains a challenge to the realization of development interventions.